Climate Effects on Firn Permeability Are Preserved Within a Firn Column. Issue 3 (19th March 2019) - Keegan, K. M.; Albert, M. R.; McConnell, J. R.; Baker, I.
Abstract: We have investigated the impacts of short‐term climatic events on firn‐permeability evolution, by analyzing density and permeability measurements from the NEEM 2009 S2 firn core from the North Greenland Eemian Ice Drilling (NEEM) site in Greenland. Our results indicate that the firn layers from 27.4 to 34.9‐m depth display the expected density but unexpected permeability values, indicating a change in firn permeability during the years 1917 to 1940. The δ 18 O and accumulation rates from a compilation of NEEM shallow cores indicate that 1928, 1929, and 1933 were significantly warmer years, and that 1928 and 1933 also had significantly higher accumulation rates. These results suggest that the sharp rise in Arctic temperature during the late 1920s and early 1930s caused metamorphism of the near‐surface firn, which was preserved in the layers at depth. Conversely, the average density remained undisturbed throughout this warm period. Our results show that climate fluctuations, especially increased temperature, permanently change the firn permeability. Without taking these changes into consideration, estimates of Δage will be inaccurate. Plain Language Summary: Glacial ice is formed from the accumulation and subsequent compaction of successive snowfall events. This transition from snow to glacial ice occurs over long periods of time and creates a region at the top of the ice sheet known as the firn column. As the firn slowly reaches the density of glacial ice, pores close off into bubbles of trapped atmospheric air. Models of firn density and gas diffusion are used to estimate the age of the air bubbles, but now there is growing evidence that the firn structure has an impact on the air age. Uncertainties in the air bubble ages negatively impact scientists' ability to interpret the ancient climate. Here we analyze a firn core from the NEEM site in Greenland using density and permeability to investigate how the microstructure of firn affects gas transport through the pores. We found that short‐term shifts in climate have a permanent effect on firn permeability, which are not included in models currently used to estimate the age of the trapped air. Thus, by including the permeability of the firn in models, we can better understand how Earth's climate has changed in the past, and how it may change in the future. Key Points: Arctic warming during the 1920s and 1930s had a permanent impact on dry firn permeability in a core from NEEM, Greenland Permeability measurements capture shifts in firn that density measurements missed in a core from NEEM, Greenland Incorporating firn permeability information into models will improve the estimation of the gas age‐ice age difference